The biological activity and phytochemistry of selected Hermannia species - Essop, Ayesha Bibi (My University, 2006)
Traditional medicines form a significant part of the lives of many people around the world and in South Africa almost 60 % of people consult traditional healers in addition to the modern medical services available. Plants form a significant part of traditional healing and hence, selected species of a traditionally used plant genus, Hermannia, were chosen for biological and chemical investigation to determine a scientific basis for the traditional use of these plants. A phytochemical investigation was carried out, firstly using thin layer chromatography (TLC) and high performance liquid chromatography (HPLC) and then isolation and identification of compounds from various Hermannia species. TLC analysis indicated significant similarities between the various species with only H. saccifera displaying chemical anomalies. This was further corroborated by the HPLC analysis although very conservative profiles were produced. Isolation of compounds from H. saccifera yielded a novel labdane compound, E-17, 19-diacetoxy - 15 - hydroxylabda - 7,13 - diene, as well as two flavones, 5,8- dihydroxy-6,7,4’- trimethoxyflavone and cirsimaritin which have previously been isolated. In addition, two commonly found compounds, lupeol and β- sitosterol were isolated from H. cuneifolia and H. salviifolia respectively. This is the first report on the isolation and identification of all five compounds from Hermannia species. Antimicrobial activity was assessed using two methods i.e. minimum inhibitory concentrations as well as the death kinetics assay. Minimum inhibitory concentrations were determined using four Gram-positive and two Gram-negative bacteria as well as two yeasts. All species investigated indicated antimicrobial activity with H. saccifera showing good activity against S. aureus and B. cereus. E-17, 19-diacetoxy - 15 - hydroxylabda - 7,13 - diene isolated from H. saccifera indicated activity (MIC = 23.6 μg/ml against S.aureus) although the activity was less than that of the crude extract (MIC = 19.5 μg/ml), thus, demonstrating that there are a number of compound contributing to the promising activity of the crude extract. This was further corroborated by the bioautograms developed of the H. saccifera extract. Time-kill studies on H. saccifera against S. aureus indicated that at concentrations of 0.1, 0.25 and 0.5 % bacteriostatic activity was observed while at 0.75% the extract achieved complete bactericidal activity after 240min. Free radical scavenging activity was assessed using the 2,2-diphenyl-1-picrylhydrazy (DPPH) and 2,2′-azino-bis(3-ethyl-benzthiazoline-6-sulfonic acid) (ABTS) assays. Ten of the twelve species indicated good activity with H. cuneifolia demonstrating the most promising activity (IC50 = 10.26 μg/ml for DPPH and 10.32 μg/ml for ABTS). Two of the isolated compound, 5,8- dihydroxy-6,7,4’- trimethoxyflavone and cirsimaritin displayed insignificant activity. The 5-lipoxygenase assay was used to assess the anti-inflammatory activity of Hermannia species. All species exhibited intermediate activity with the exception of H. cuneifolia (IC50 = 15.32 μg/ml). In addition, four isolated compounds, 5,8- dihydroxy-6,7,4’- trimethoxyflavone, cirsimaritin, lupeol and β-sitosterol showed moderate inhibition of the enzyme indicating that while these compounds do contribute to the activity of the extracts they are not individually responsible for any significant activity. Antimalarial activity was assessed using the titrated hypoxanthine incorporation assay while toxicity was assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) cell proliferation assay. Only three species indicated any good antimalarial activity i.e. H. saccifera, H. muricata and mostly H. trifurca (IC50 = 25.30, 28.17 and 18.80 μg/ml respectively). However, the activity of H. saccifera and H. trifurca are probably due to a general cytotoxicity as these species exhibited a low safety index. All other species appear safe for use. Several Hermannia species have indicated in vitro biological activity in a number of assays which is related to their use in traditional medicines to treat a number of disease states. Hence, a scientific basis, albeit in vitro, has been established for the use Hermannia species in traditional healing.
Student Number : 0000127R - MPharm dissertation - School of Pharmacy and Pharmacology - Faculty of Health Sciences
Keywords: biological activity; phytochemistry; hermannia; antimicrobial; antioxidant; anti-inflammatory; anti-malarial